Optymalizacja struktury finansowania krótkoterminowego w przedsiębiorstwie - metoda portfelowa - Szałański, Mariusz (How to Optimize Corporate Short-Term Capital Structure - A Portfolio Method, 2008)
The purpose of this article is to illustrate how portfolio methods can be effectively applied to optimize the structure of corporate external short-term capital. The portfolio method has been broadly used to search for and find the optimum structure of income-generating factors (such as shares or liabilities in enterprises) belonging to two categories: related to risk (measured with volatility rate) and to income. However, it seems that the portfolio method may find an equally effective application in optimizing the structure of external sources of short-term capital based on two dimensions: risk (volatility measure) and cost.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 528-536